Study on Vertical Profile of 210Pb and Sedimentation Rate at Pantai Remis Coastal Area and Kuala Selangor Estuary - Kalsum Abdul Karim, Umi; Saat, Ahmad; Izzharif Abdul Halim, Mohamed (International Journal of Engineering and Technology, 2018)
Two sediment cores in Kuala Selangor estuary and Pantai Remis coastal area were obtained using gravity corer and then were analyzed using Alpha Spectrometry System. In order to estimate the sedimentation rate in the area, 210Pb dating technique and Constant Rate & Supply (CRS) model were used. From the study, the vertical profile of 210Pb shows a decreasing trend with depth and finally achieving a constant level. Based on the vertical profile of 210Pb, activity of excess 210Pb was obtained and was used to determine the sedimentation rate in the study area. Pantai Remis coastal area shows high sedimentation rate than Kuala Selangor estuary which may due to high sediment input in the area. Besides, the differences in sedimentation rate might be attributed to highly variable sedimentary and hydrodynamic conditions in the estuary and coastal area.Â Â